Development Possibilities of Backward Areas in Hungary - Faragó, László; Hrubi, László (Discussion Papers, 1988)
The presence of development aiming at creating a balanced structure is desirable not only on account of socio-political and social reasons but also in view of the efficient functioning of society and economy. Development policy with strong internal priorities aimed at extensive-quantitative growth results in a polarized regional structure inevitably creating backward areas where disadvantages are being accumulated. In the absence of an efficient development policy aimed at an equalized regional structure, over polarization may arise and the decline of certain areas will become irreversible. The present study explores the development possibilities of backward zones in Hungary. After introducing the characteristic features of the multiple-disadvantaged situation, the authors outline two alternative (socio-political and economico-political) approaches to making these zones catch up with the others. An individual chapter introduces the long-term development conception of the multiple-disadvanted zones. The final section of the study sheds light on the peripheric position of multiple-disadvantaged zones in administration and organization. The authors arrive at the conclusion that the moderation and occasional elimination of backwardness can be accomplished only by an integrated long-term development strategy aimed at influencing the development processes of settlements and regions.